On the Issue of New Risks in the Information Sphere and Implementation of the Principle “Security through Development” - Oleg S. Makarov (Евразийская интеграция: экономика, право, политика)
The article considers the essence and content of information security based on a phenomenological analysis of emerging social relations in the context of “explosive informatization”. Based on the principle of “security through development”, the results of a comparative legal study of legislative innovations in the field of information and legal transformation of Belarus and Russia are presented. The strategic directions of further legal regulation are determined, ensuring the anticipation of new risks and challenges.